A comparison of driving related skills impaired by ethanol and zopiclone. (2nd January 2021) - Høiseth, Gudrun; Hjelmeland, Knut; Mørland, Jørg
Abstract: Objective: Ethanol and zopiclone are both sedating drugs that impair traffic relevant skills, but that show vast differences in epidemiological traffic risk. One explanation for this could be that they impair various kinds of skills differently, but this is less previously studied. The aim of this study was to compare effects of zopiclone and ethanol on a large battery of computerized psychomotor and cognitive tests according to different test classifications. Methods: Ethanol (50 grams), zopiclone 5 mg, zopiclone 10 mg or placebo was administered in a randomized trial with a cross-over design. Blood was sampled nine times after administration and analyzed for zopiclone and ethanol using fully validated methods. The computerized tests Connors Continuous Performance Test (CPT), Stockings of Cambridge (SOC) and choice reaction time (CRT) was performed at baseline and after administration. The three tests yielded fifteen different test components, which were categorized according to the three well-known behavior levels (automative behavior, control behavior and executive planning). Secondly, they were categorized into tests measuring "reaction time", "impulsivity" and "attention/cognition". Results: On all tests belonging to behavior level 1 and on all tests measuring "reaction time", more subjects were impaired by zopiclone than ethanol. On all tests measuring "impulsivity", more subjects were impaired by ethanol than zopiclone. Conclusion: Zopiclone and ethanol both lead to impairment, but have a different profile on what kind of tests and neurocognitive functions they mostly impair. This could be important in the understanding of the differences in traffic risk connected to these two drugs.